PENGARUH PENERAPAN E-SYSTEM PERPAJAKAN, INSENTIF PERPAJAKAN, SANKSI PERPAJAKAN, DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK SELAMA MASA PANDEMI (Studi pada Wajib Pajak terdaftar di KPP Pratama Jepara) - Malida Salma Arum Ndalu; Djoko Wahyudi (Universitas Sains dan Teknologi Komputer, 2022)
This study aims to examine the effect of the e-system of taxation, tax incentives, taxvsanctions, and service quality on individual taxpayer compliance in paying taxes. This research was conducted on individual self-employed taxpayers registered at KPP Pratama Jepara. This research is a quantitative research using primary data sources with distribution via google form link. The population in this study were all takxpayers who are independent workers who are registered at KPP Pratama Jepara. The data analysis technique used multiple linear regression analysis wich was processed in the SPSS version 24 program. The result showed that the e-system of taxation, tax incentives, tax sanctions, and service quality had a significant positive effect on taxpayer compliance.